Desain dan Ujicoba Buletin Berbasis SETS (Science, Environment, Technology and Society) dengan Menggunakan Adobe Flash Cs6 Pada Materi Larutan Elektrolit dan Nonelektrolit - Siti Aminah; Neti Afrianis (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2023)
The lack of use of learning media that can help students in the learning process and connect learning materials with everyday life is the background of this research. This study aims to develop a media bulletin based on SETS (Science, Environment, Technology, and Society) using Adobe Flash CS6 to support learning in the subjects of Electrolyte and Non-Electrolyte solutions. Research and Development (R&D) with the Borg and Gall model. Observations, interviews, and questionnaires are the techniques used to collect data. The data collection instruments were interview guides, observation sheets, validity, practicality, and student response questionnaires. The SETS-based bulletin that was developed was tested with a percentage of 90.14% (very valid), practical tested with a percentage of 91.96% (very practical), and received responses with a percentage of 90.78% (very practical). Based on these findings, it can be said that the SETS-based Bulletin using Adobe Flash CS6 in supporting the learning of Electrolyte and Non-Electrolyte subjects is valid and practical, so it can be tested further.